Terörün sosyolojisi: Toplumsal kökenleri anlama imkanı - (:unkn) unknown (My University, 2010)
Küresel ve ulusaşırı nitelik kazanan şiddet ve terör eylemlerinin, bölgesel ve uluslararası ilişkileri gerginleştirerek güvenlik eksenine çektiği görülmektedir. Şiddet ve terör eylemlerini analiz eden çalışmaların çoğu, ağırlıklı olarak söz konusu eylemlerin güvenlik boyutu üzerinde durmaktadır. Terörün toplumsal kökenleri üzerinde ise yeterince durulmadığı gözlenmektedir. Bu makale, son yıllarda yayınlanan bilimsel literatür ışığında terörün sosyolojisi üzerinde durma ve kökenlerini analiz etmenin önemine işaret etmeyi amaçlamakta; disiplinlerarası yöntem ve yaklaşımlara dayalı bir “teroroloji/terör bilimi”nin gereğini vurgulamaktadır. Çünkü şiddet ve terör eylemlerinin toplumsal bağlamı çözümlenmeden bu tür olaylarla etkin biçimde mücadele edilmesi mümkün olmayacak ve uluslararası ilişkileri olumsuz yönde etkilemeye devam edecektir.

Organized violence and terrorist attacks with global connections and transnational implications not only contribute to the deterioration of regional and international relations but also tend to locate and confine international relations analysis to the axis of securitization. Much of the studies on collective violence and terrorism focus on security aspects of such acts but fail to address social roots of confl icts adequately. This article seeks to draw attention to the significance of sociological analysis of acts of terrorism in light of recent scholarship. It argues that without a thorough analysis of social contexts of such acts, fi ghting terrorism and violence will not be effective and international relations will deteriorate further. Therefore the article concludes that a ‘sociology of terrorism’ based on interdisciplinary method and approach will complement international relations theory and provide rational grounds to take effective policy measures against acts of terror.
Sociology of terrorism: A key to understanding social origins?
Keywords: Uluslararası İlişkiler; Siyasi Bilimler